2021
DOI: 10.3390/cancers13112529
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Targeted Therapy in BRAF Mutant Advanced Melanoma Patients: Results from a Multicenter Retrospective Observational Study Advanced Melanoma in Russia (Experience) (ADMIRE)

Abstract: Clinical trials of targeted therapy (TT) and immunotherapy (IT) for highly aggressive advanced melanoma have shown marked improvements in response and survival rates. However, real-world data on treatment patterns and clinical outcomes for patients with advanced BRAF V600 mutant melanoma are ultimately scarce. The study was designed as an observational retrospective chart review study, which included 382 patients with advanced BRAF V600 mutant melanoma, who received TT in a real-world setting and were not invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
(32 reference statements)
2
5
2
1
Order By: Relevance
“…Analyses performed excluding these patients led to the same results (data not shown). Previous real-world research showed a statistically significant difference in PFS and OS for different V600 mutations [19]. In the real-world population, subsequent anticancer therapy was used in 52% of the patients, which was comparable to data from the COMBI-v and -d trial (53%) and the coBrim trial (51%) [5,17].…”
Section: Trials Vs Real-worldsupporting
confidence: 67%
“…Analyses performed excluding these patients led to the same results (data not shown). Previous real-world research showed a statistically significant difference in PFS and OS for different V600 mutations [19]. In the real-world population, subsequent anticancer therapy was used in 52% of the patients, which was comparable to data from the COMBI-v and -d trial (53%) and the coBrim trial (51%) [5,17].…”
Section: Trials Vs Real-worldsupporting
confidence: 67%
“…In the 382 included patients the ORR to the combined BRAF/MEK inhibitor and to the BRAF inhibitor mono-therapy were 57.4% and 39.8%, respectively. The median PFS and OS were 9.2 months and 22.6 months, respectively, for the combined first-line therapy; 9.4 months and 16.1 months, respectively, for the combined second-line therapy; and 7.4 months and 17.1 months, respectively, for the combined third or higher-line therapy [12]. The results of this study were similar to those in clinical trials and better than those in other real-world data studies.…”
Section: Discussionmentioning
confidence: 97%
“…BRAFi plus MEKi combination therapy has demonstrated improved efficacy compared with BRAFi alone and is the standard TT option for patients with BRAF+ melanoma, which could explain the difference in findings between this study and ours. Moreover, this sequencing analysis included a small number of patients ( n = 123), with only 31 patients in the IO before TT group and 92 patients in the IO after TT group, and it was unclear whether this analysis was adjusted for baseline differences between groups [14].…”
Section: Discussionmentioning
confidence: 99%
“…One other study by Orlova et al . [14] found that patients who received IO (anti-PD1) before TT demonstrated a significantly higher survival rate compared to those who started IO after TT. The TT group in this study, however, included both patients who received BRAF inhibitor (BRAFi) monotherapy and those who received BRAFi plus MEK inhibitor (MEKi) combination therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation